Early Cretaceous granitic aplite in the Gaozhuang gold deposit, northern Qinling Orogenic Belt, central China: Implications for petrogenesis and metallogenesis. (7th April 2021) - Liang, Tao; Lu, Ren; Li, Longming
Abstract : Petrogenesis of the Gaozhuang granitic aplites (GZGA) plays an important role in understanding the regional tectonic evolution and metallogenesis of the Gaozhuang gold deposit (GZGD) in the northern Qinling orogenic belt (NQOB). Here, we present new zircon U–Pb dating on two granitic aplite samples yielding a 25‐zircon grain weighted average age of 129 ± 1 Ma (MSWD = 0.6), suggesting that GZGA formed in the Early Cretaceous. Major element results show that GZGA are: (a) characterized by higher SiO2 and alkali and lower MgO and CaO, belonging to the high‐K calc–alkaline series; (b) enriched in large‐ion lithophile elements and depleted in high‐field‐strength elements, which show negative spider–diagram anomalies of Nb, Ta, P, and Ti; (c) enriched in light rare earth elements and depleted in heavy rare earth elements without obvious Eu negative anomalies and (La/Yb) N ratios ranging from 71.9–107. GZGA compositional variation is controlled mainly by source composition and degree of partial melting and suggests no obvious relationship with fractional crystallization. GZGA samples belongs to the adakite, showing higher Sr (346–528 ppm), lower in Y (4.71–5.67 ppm) and Yb (0.26–0.33 ppm), and Sr/Y ratios of 63.5–93.2, indicating that GZGA originated from partial melting of the thickened lower crust (source depth >50 km) with residual phases of garnet, rutile, and insignificant plagioclase. Results find that GZGA is a product of the Early Cretaceous regional lithosphere delamination, in which Gaozhuang area adakitic aplite magmas and ore‐bearing fluids were discharged nearly simultaneously, and the mixed magma–fluid systems crystallized, forming GZGA and GZGD, while rapidly ascending to the shallow crust along faults. Using GZGA, a prospecting indicator, we infer that the deep part of the GZGD should possess endogenetic Au metallogenic potential. Abstract : The Gaozhuang granitic aplite in the northern Qinling Orogenic Belt, central China, belongs to adakite. The Gaozhuang granitic aplite is one of geological products of lithosphere delamination in ~129 Ma. The Gaozhuang granitic aplite is one of prospecting indicators, and the Gaozhuang gold deposit possesses endogenetic metallogenic potential.